CLUSTER ANALYSIS USING AFFINITY COEFFICIENT IN ORDER TO IDENTIFY RELIGIOUS BELIEFS PROFILES - Sousa, Aurea; Nicolau, Fernando C.; Bacelar-Nicolau, Helena; Silva, Osvaldo (European Scientific Journal, ESJ, 2014)
We present an application of Ascendant Hierarchical Cluster Analysis (AHCA) to a dataset related to religion, in order to find a typology of religious beliefs profiles of individuals who live on São Miguel island (Azores) according to the frequency they go to the Mass. AHCA was based on the weighted generalized affinity coefficient for symbolic or complex data, and on classical and probabilistic aggregation criteria; the probabilistic ones belong to a parametric family of methods in the scope of the VL methodology. Additionally, we applied some validation measures (based on the values of the proximity matrix and adapted for the case of similarity measures) to evaluate the obtained results (clusters and partitions).